Comparative pharmacokinetics of porcine and human anti-influenza hemagglutinin monoclonal antibodies in outbred pigs and minipigs - Paudyal, Basudev; Moorhouse, Elliot; Sharma, Bhawna; Dodds, Michael; Nguyen, Victor; Milad, Mark; Tchilian, Elma (Frontiers in Immunology, 2024)
Assessing pharmacokinetics of monoclonal antibodies (mAbs) in relevant animal models is essential for designing improved formulations and developing mAb delivery platforms. We have established the pig, a large natural host animal for influenza with many similarities to humans, as a robust model for testing the therapeutic efficacy of anti-influenza mAbs and evaluating mAb delivery platforms. Here we compared the pharmacokinetic characteristics of two anti-influenza hemagglutinin mAbs, human 2-12C and porcine pb27 in Göttingen minipigs and Landrace × Large White outbred pigs. Minipigs offer the advantage of more stable weight, while outbred pigs are more readily available but exhibit rapid growth. Both outbred and minipigs showed similar pharmacokinetics and half-life of porcine pb27 (half-life of 15.7 days for outbred and 16.6 days for minipigs). In contrast, the half-life of human 2-12C was more rapid in two of the minipigs, but not in the outbred pigs, correlating with the development of antidrug antibodies (ADA) in the two minipigs. Our results demonstrate that both outbred and minipigs are appropriate models for pharmacokinetic studies and evaluation of mAb delivery platforms, potentially bridging the gap between small animals and human trials.